Identification of MEDAG and SERPINE1 Related to Hypoxia in Abdominal Aortic Aneurysm Based on Weighted Gene Coexpression Network Analysis - Teng, Biyun; Xie, Chaozheng; Zhao, Yu; Zeng, Qiu; Zhan, Fangbiao; Feng, Yangyang; Wang, Zhe (Frontiers in Physiology, 2022)
Abstract Purpose: Abdominal aortic aneurysm (AAA) is a severe cardiovascular disease that often results in high mortality due to sudden rupture. This paper aims to explore potential molecular mechanisms and effective targeted therapies to prevent and delay AAA rupture. Methods: We downloaded two microarray datasets (GSE98278 and GSE17901) from the Gene Expression Omnibus (GEO) database. The differential analysis and single sample gene set enrichment analysis (ssGSEA) hypoxia scores were performed on 48 AAA patients in GSE98278. We identified hypoxia and ruptured AAA-related gene modules using weighted gene co-expression network analysis (WGCNA). Gene Ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) analyses were performed using the R package clusterProfiler. For candidate genes, validation was conducted in the mouse dataset (GSE17901). Finally, we predicted drug candidates associated with hub genes using the HERB Chinese medicine database. Results: 82 differential genes were screened in ruptured and stable groups; 103 differential genes were identified between high and low hypoxia groups; WGCNA identified 58 differential genes. Finally, 9 candidate genes were screened, including 2 hub genes (MEDAG and SERPINE1). Meanwhile, we identified pathways such as Cytokine-cytokine receptor interaction and T-helper 1 type immune response involved in AAA hypoxia and rupture. We predicted 93 Traditional Chinese medicines (TCM) associated with MEDAG and SERPINE1. Conclusions: We identified the hypoxic molecules MEDAG and SERPINE1 associated with AAA rupture. Our study provides additional direction for the association between hypoxia and AAA rupture.